Effect of apple vinegar treatment on life variables related to renal function in male rats - Intesar Taha (مجلة التربية والعلم, 2006)
The research involves the study of effect of apple vinegar on some of biochemical parameters which are related to renal function in experimental male mice of Swiss type. Their weight ranged from (25-30) gms. The mice .were divided into two groups. The first group was treated with distilled water (control). The second group was treated with diluted apple vinegar by rate 1 water : 3 Apple vinegar by 5ml/kg of body weight . The solution was orally (once daily) administered for three weeks after first, second , and third week of administration blood samples were obtained from the eye-socket. Spectrophometric method was used to determine the biochemical parameters the results showed that (dil) apple vinegar decreased the level of protein, albumin & globulin and decreased the level of uric acid, urea & creatinine in the blood.